Nurses’ experiences of text-based digital triage at primary healthcare centres in Sweden: a qualitative interview study - Ester Rydell; Ulf Jakobsson; Sigrid Stjernswärd (BMC Nursing)
Abstract Background Telehealth services are becoming increasingly popular at primary healthcare centres. Some examples include text-based digital triage and health guidance using chats, emails, images and pre-filled forms. Telephone-based communication has until recent years been the predominant means for triage and health guidance, but now includes written communication via computer or smartphone. Hence conditions to perform triage and health guidance have changed, which may affect the quality of nurses’ work and patient safety. This motivates an in-depth exploration of the consequences of such changes for nurses working with telehealth. The study aimed to explore nurses’ experiences of digital triage and health guidance at primary healthcare centres in Sweden. Methods A qualitative inductive design was chosen for the current study. Four registered nurses and two public health nurses, working at primary healthcare centres in southern Sweden, contributed with information about text-based digital triage and health guidance. Semi-structured interviews were conducted to collect data. Data were analysed using qualitative content analysis. Findings One main theme, “Adapting to a new professional toolbox to triage and give health guidance” was constructed based on three categories which describe the altered professional tools. They were: “Using one’s senses differently to collect information”, “Change of communication mode to convey messages” and “Change of timeframe and the use of time”. Six subcategories describe how the new toolbox was experienced by the nurses. They were: “Loss of clinical ear”, “Gain of viewing images”, “Difficulties in written communication of care and emotions”, “Seeing oneself as a writer or talker”, “Tardy asynchronous communication” and “Available time”. Conclusion The findings tell of a substantial change in nurses’ professional toolbox that demanded other skills than they were used to working with. Due to limitations in communication and communication skills, digital triage alone may lead to an impaired workflow, quality of care, and patient safety as well as maintain the digital divide. However, digital triage may also enhance nurses’ work with the addition of attached images, convenient communication for those who are comfortable with writing, and a gain of time for consultation and reflection. The current study contributes insights regarding new competencies that nurses and patients must have or gain to be able to benefit from the possibilities of digitisation of primary healthcare.